Photocatalytic degradation of organic compounds using carbon based composite catalysts - Zhou, Guanliang (Curtin University, 2013)
In recent decades, the applications of advanced oxidation processes (AOPs) for organic pollutants treatment in wastewater have been thoroughly investigated. These techniques base on chemical destruction and give a complete solution to the problem of wastewater containing toxic organics. Among these processes, semiconductor-based photocatalytic process has been employed as a low-cost, environmentally friendly and sustainable technique to purify water/wastewater. Meanwhile, chemical oxidation process is also considered as an effective remediation technique to reduce the concentrations of targeted toxic organics in wastewater to acceptable levels.The aim of this work is emphasizing the role of new synthesized catalysts in advanced oxidation process for wastewater treatment. The key conclusion of this thesis is that novel photocatalysts being capable to degrade organics in aqueous phase at room temperature were successfully synthesized and the investigation of “green cobalt based catalysts” for degradation of organic pollutants via advanced oxidation processes was achieved. Various types of catalysts were synthesized with hydrothermal carbonization method or wet impregnation method, and used for degradation of phenol in aqueous phase with UV-vis and visible light irradiation. Titanates: ZnTiO3, FeTiO3 and Bi4Ti3O12 were modified by coating cobalt (Co) to prepare photocatalysts. Microcarbon spheres were also synthesized by hydrothermal method, and used to support TiO2 (C-TiO2), nanoscaled zerovalent iron (nano-Fe0@CS), cobalt (micro-CS@Co) and graphitic carbon nitride (C-g-CN). All of these catalyst materials were tested for phenol degradation. Some of these synthesized catalysts were also examined for activating peroxymonosulfate (PMS, Oxone) for the decomposition of phenol.